O artificialismo tardio de Jean Renoir: teatralidade e crítica - Cícero Pedro Leão de Almeida Oliveira (2019)
The research investigates the films The golden coach (1952) and Luncheon on the grass (1959), directed by Jean Renoir. We seek to identify how the stylistic and dramaturgical choices of the director configure in these films a stylized artificialism with theatrical references, characteristic of his artistic phase in the 1950s. From the analysis of mise-en-scène and dramaturgy, we investigate how such artificialism results in a playful and incisive perspective on relationships in society. In order to better characterize the critical dimension of the late artificialism of Renoir's work, we present a review of the theatricality in the director's earlier work and we studied debates on the relationship between theater and cinema, both conceptually and formally, particularly important for the first cinema of the century XX, to which Renoir's work is linked. Next, we discuss how the two films of the corpus rescue elements of expressive theatricality to build their worlds and their critical visions.